PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN ALAT PERAGA MEQIP PADA SISWA KELAS V SDN 001 SAMARINDA - Eka Juliatin; Nurul Hikmah; Eka Selvi Handayani (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This study aims to determine the increase in motivation and learning outcomes of mathematics in flat wake material in fifth grade students of SDN 001 Samarinda. The benefits of this study are for students to be more motivated in learning and teachers can improve the quality of education in the classroom. This type of research is PTK, conducted at SDN 001 Samarinda, class V (33 students) and one class teacher. Data collection techniques are observation, written test, documentation. The results of this study indicate that student learning outcomes can improve. This is evidenced by the existence of an increase in the average learning outcomes, in the first cycle the average grade of 55.92 with a classical percentage of 27%, the second cycle of the average grade of 75.75 with a classical percentage of 70%, in the third cycle the average value class 81,15 and the classical percentage is 94%. The conclusion of the study from cycle I to cycle III motivation and learning outcomes of students in grade V SDN 001 Samarinda, there was an increase in each cycle.Keywords : Motivation, Learning Outcomes, Flat Build, MEQIP Props